A Stylistic Analysis of Conflict Mediation Discourse in a Literary Test - Adegbite, Wale (2014)
The study does a stylistic study of an extract of conflict mediation discourse from Chinua Achebe's Things Fall Apart. It analyses the linguistic patterns that realise theme, transitivity, mood and modality in the extract. The goal is to make students observe the stylistic means by which the author has expressed content in English. The extract represents the speech of a character that has attempted to resolve a conflict in the novel. The linguistic stylistics approach is employed in the study and the linguistic theories utilized are Systemic Functional Linguistics and the Functional Sentence Perspective. Apart from demonstrating the application of linguistics to the interpretation of literary texts, the study projects the artistic qualities of content and form embodied in the novel. The study has relevance for the areas of rhetoric, stylistics, register studies and, particularly, for English Studies in an ESL situation.